2015
DOI: 10.1089/jmf.2014.0065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wild Blueberry Consumption on Plasma Markers and Gene Expression Related to Glucose Metabolism in the Obese Zucker Rat

Abstract: Impaired fasting blood glucose is one of the landmark signs of metabolic syndrome, together with hyperinsulinemia, dyslipidemia, hypertension, and a chronic proinflammatory, pro-oxidative, and prothrombotic environment. This study investigates the effect of wild blueberry (WB) consumption on blood glucose levels and other parameters involved in glucose metabolism in the obese Zucker rat (OZR), an experimental model of metabolic syndrome. Sixteen OZRs and 16 lean littermate controls (lean Zucker rat [LZR]) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
0
34
0
Order By: Relevance
“…Following the above mentioned studies, Vendrame et al [43] reported that supplementation with 8% (wt/wt) wild blueberry powder (WBP) after 8 weeks of feeding significantly increased blood adiponectin levels as well as reduced the levels of inflammatory markers in WAT [43] and improved dyslipidemia [6]. However, WBP did not obtain reduced fasting blood glucose (FBG) and insulin levels in obese Zucker rats in this study [44]. …”
Section: The Role Of Anthocyanins In Obesity: Animal Studiesmentioning
confidence: 70%
“…Following the above mentioned studies, Vendrame et al [43] reported that supplementation with 8% (wt/wt) wild blueberry powder (WBP) after 8 weeks of feeding significantly increased blood adiponectin levels as well as reduced the levels of inflammatory markers in WAT [43] and improved dyslipidemia [6]. However, WBP did not obtain reduced fasting blood glucose (FBG) and insulin levels in obese Zucker rats in this study [44]. …”
Section: The Role Of Anthocyanins In Obesity: Animal Studiesmentioning
confidence: 70%
“…In opposition to the previous positive anti-diabetic blueberry studies, other researchers documented no influence of blueberries on insulin resistance and/or glucose tolerance in obese mice and rats [15,27,28,29]. Although Vendrame and Colleagues [29] did not observe any significant changes on HOMA-IR with blueberry supplementation, they did find significant biological changes in the glucose metabolism related plasma markers (hemoglobin A1c, retinol-binding protein 4, and resistin concentrations).…”
Section: Anti-diabetic Effect Of Blueberriesmentioning
confidence: 87%
“…Although Vendrame and Colleagues [29] did not observe any significant changes on HOMA-IR with blueberry supplementation, they did find significant biological changes in the glucose metabolism related plasma markers (hemoglobin A1c, retinol-binding protein 4, and resistin concentrations). These markers were lower in the obese Zucker rats that consumed a 8% blueberry diet for 8 weeks when compared to the rats that did not consume blueberries.…”
Section: Anti-diabetic Effect Of Blueberriesmentioning
confidence: 92%
See 1 more Smart Citation
“…The effects of wild blueberry on blood glucose levels and other parameters involved in glucose metabolism were investigated in obese Zucker rats [30]. Wild blueberries are one of the richest fruit sources of anthocyanins, a class of phenolic bioactive compounds that have been shown to have insulin-sensitizing effects and to improve glucose utilization.…”
Section: In Vitro and In Vivo Effects On Carbohydrate Metabolismmentioning
confidence: 99%